Technological Aspects in the Era of Digital Transformation Leading to the Adoption of Big Data - Lutfiani, Lucia Sausan; Birgithri, Andzelika; Queen, Zabenaso (Startupreneur Business Digital (SABDA Journal), 2024)
The purpose of this study is to examine how technical advancements have impacted big data analytics adoption in the age of digital transformation. The study's population consists of Indonesian businesses who have integrated big data into their operational systems, particularly those in Jabodetabek. 205 individuals were included in the study's sample through the use of a purposive sample technique. Primary data from a questionnaire survey are the sort of data used in this study. Using SPSS version 25, several regression approaches were used to examine the data. The study's findings indicate that businesses' interest in implementing big data is positively impacted by relative advantage, compatibility, and complexity. However, security has a negative impact on businesses' willingness to use big data.